Mating type (MAT) locus and possible sexuality of the opportunistic pathogen Exophiala dermatitidis - Metin, Banu (Fungal Genet Biol, 2019)
Sexual reproduction among the black yeasts is generally limited to environmental saprobic species and is rarely observed among opportunists in humans. To date, a complete sexual cycle has not been observed in Exophiala dermatitidis. In this study, we aimed to gain insight into the reproductive mode of E. dermatitidis by characterizing its mating type (MAT) locus, conducting MAT screening of environmental and clinical isolates, examining the expression of the MAT genes and analyzing the virulence of the isolates of different mating types. Similar to other members of the Pezizomycotina, the E. dermatitidis genome harbors a high mobility group (HMG) domain gene (MAT1-2-1) in the vicinity of the SLA2 and APN2 genes. The MAT loci of 74 E. dermatitidis isolates (11 clinical and 63 environmental) were screened by PCR, and the surrounding region was amplified using long-range PCR. Sequencing of the ~12-kb PCR product of a MAT1-1 isolate revealed an α-box gene (MAT1-1-1). The MAT1-1 idiomorph was 3544-bp long and harbored the MAT1-1-1 and MAT1-1-4 genes. The MAT1-2 idiomorph was longer, 3771-bp, and harbored only the MAT1-2-1 gene. This structure suggests a heterothallic reproduction mode. The distribution of MAT among 74 isolates was ~1:1 with a MAT1-1:MAT1-2 ratio of 35:39. RT-PCR analysis indicated that the MAT genes are transcribed. No significant difference was detected in the virulence of isolates representing different mating types using a Galleria mellonella model (P>0.05). Collectively, E. dermatitidis is the first opportunistic black yeast in which both MAT idiomorphs have been characterized. The occurrence of isolates bearing both idiomorphs, their approximately equal distribution, and the expression of the MAT genes suggest that E. dermatitidis might reproduce sexually.